In vitro study of the antibacterial and anticancer activities of silver nanoparticles synthesized from Penicillium brevicompactum (MTCC-1999). Issue 4 (1st October 2016) - Majeed, Shahnaz; Abdullah, Mohd Shafyiq bin; Nanda, Anima; Ansari, Mohammed Tahir
Abstract: Among the most promising nanomaterials, metallic nanoparticles with antibacterial and antitumor properties are expected to open new avenues to fight and prevent various tumours and infectious diseases. The study of bactericidal nanomaterial is particularly timely considering the recent increase in new resistant strains of bacteria to the most potent antibiotics and the potential role of bactericidal nanomaterial as anticancer agents. This has promoted the research of the well-known activity of silver ions and silver-based compounds, including silver nanoparticles. The present work is the study of silver nanoparticles synthesized from Penicillium brevicompactum (MTCC-1999). The colour of the cell filtrate changes to dark brown upon addition of 1 mM AgNO3, suggesting the formation of silver nanoparticles. These silver nanoparticles (AgNPs) were characterized and analyzed by UV–vis spectrophotometric analysis, which showed a peak of absorbance at 420 nm. Fourier transform infrared (FTIR) analysis showed amines and amides that are responsible for the stabilization of AgNPs. To determine the particle size, atomic force microscopy (AFM) analysis was used, which showed that the nanoparticles are spherical and are 30–50 nm in size. High-resolution transmission electron microscopy (HRTEM) showed that AgNPs were well dispersed, spherical, and well within the range of 40–50 nm. These nanoparticles displayed good antibacterial activity and also increased the antibiotic activity of gatifloxacin, tetracycline, and vancomycin. These nanoparticles were further studied for their anticancer activity and showed high toxicity towards the MCF-7 breast cancer cell line.